Plataforma computacional híbrida de coprocessamento paralelo distribuído por web services aplicada à radiointerferometria - Silva, Gustavo Poli Lameirão da (2013)
The requirements imposed by the new applications presents great challenges to the computation. There is not a perfect computer architecture, capable to attend to all the requirements. The parallel and hybrid computer arrangement rise as a solution to this scenario i.e., the CPU-Coprocessor pair arrangement can form a specialized computerized instrument for a special application task. This doctoral thesis proposes a parallel and hybrid computational platform denoted CoP-WS, that uses the interoperability technology known as Web Services. As coprocessor it is used the graphic processing unit, known as the GPU, functioning recently as parallel thread level processing of general use applications. The platform test of feasibility was inspired in radio astronomy, and it has been implemented two applications: a complex correlator of signals provided by a radio interferometric arrangement, and a flare recognition system with a solar radio interferometer image. Both processings can be inserted in the context of pipeline execution, using sufficient configuration of CPU-GPU pairs, having on one side the interferometric arrangement antenna signal input and in the other side the result of the solar flare recognition. The obtained results of the both applications show the feasibility of the CoP-WS platform, for greater volume of data being processed in quasi real time. In the case of the correlator the average processing time in each integration period was around 160 ms, and in the case of the solar flare recognition, 48 ms for each solar disk image.